Plan de marketing digital para fidelizar a los clientes de la microempresa Mundo Móvil del cantón Marcabelí - Japón Ríos, Nardy Rosibel (2022)
The general objective of this research work is to develop a digital marketing plan to build customer loyalty of the microenterprise Mundo Móvil in Marcabelí canton, so that the owners can communicate and interact with users through digital media to keep them. The four specific objectives were also met, first conducting an external situational diagnosis covering the PESTE analysis to make the EFE matrix with the most relevant threats and opportunities, also the competitive analysis and Porter's 5 forces to determine how the competition is using observation sheets for information collection, then the internal part was investigated to create the EFI matrix with the strengths and significant weaknesses, along with the Ansoff analysis and the product portfolio (BCG); Subsequently, the information was compiled to create the SWOT with its respective matrix to propose strategies that help to fulfill the purpose of this research. For the second objective, customers were surveyed to know the tastes and preferences in accessories and digital media they frequent, at the same time the owners were interviewed to know how they manage the business. In relation to the third objective, micro and macro strategies were designed, based on SEO, SEM and Inbound marketing so that the owners could put them into practice. Finally, the fourth objective presented the budget they will need to execute the strategies, giving a value of $ 1,412.50 dollars, then there are the conclusions, recommendations, bibliography and annexes that support the work done.